Delay in the Diagnosis of Oral Malignancy : Study on Responsible Factors - Chowdhury, Nurul Karim; U, Kyaw Khin; Chowdhury, Ziaul Answar; Uddin, Md Abbas; Hossain, HS Mubarak; Biswas, Supran; Anwar, Mostafa Mahfuzul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Oral malignancy is an emerging disease all over the world. Treatment failure is grave if the diagnosis is delayed in this disease which will ultimately increase the mortality rate. This is an observational sociodemographic study, done to identify the causes in diagnostic delay of the patients suffering from oral cancer. Materials and methods: The study was done with a sample size of 215 cases of oral cancer patients. This observational study was conducted from 1st August 2015 to 31st December 2016 at Upazila Health Complex, Mirsarai, Chattogram & later at ENT Department of Chittagong Medical College Hospital from 1st March 2017 to 30thApril 2018. Results: Several causes of diagnostic delay were identified. Among them, monetary issue (78%) and Ignorance or Illiteracy (69%) have been found as the most important causes. Stage of the disease, delay in referral system, tobacco use, age, gender, alternative medicine, social taboo ,distance of hospital from house etc were found the other factors delaying the diagnosis of the cancer. Conclusion: Many of the causes of delay can be preventable. The authority should establish awareness among the patients & a protocol for early detection of cancer by the health professionals. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 37-40